Nitrogen and phosphorous dynamics with stand development of Pinus massoniana plantations in Southeast China - Guo, Wen; Jiao, Pengyu; Lopez C, M. Larry; Chen, Zelong; Wei, Lili; Liu, Xian; Hu, Yalin; Wang, Yuzhe (Frontiers in Plant Science, 2023)
Nutrient resorption is a key mechanism to conserve nutrients and overcome nutrient limitation in perennial plants. As an important afforested tree species in subtropical regions, Pinus massoniana grows well in nutrient-poor environments, however, the age-related pattern of nutrient acquisition strategy and the underlying mechanisms in P. massoniana plantations remain unclear. In this study, concentrations of nitrogen (N) and phosphorus (P) were measured in green and senesced needles, roots and soil samples collected from P. massoniana plantations with different stand ages (9-, 17-, 26-, 34- and 43-year-old) in south China. From these samples, nutrient resorption efficiency (RE) and stoichiometry were calculated. Foliar PRE significantly decreased with stand age, while there was no clear pattern of NRE along the stand development. Green needle N:P in older stands was significantly lower than in younger ones. Senesced needle C:P and N:P significantly decreased with stand age. Root and soil available P concentrations were significantly higher in older stands than in younger ones, and PRE was negatively correlated with soil available P concentration. There was a shift from “conservative consumption” to “resource spending” P-use strategy, and P limitation decreased with stand development of P. massoniana plantations. The results provide information of changes in nutrients dynamics, which is relevant for the sustainable management of subtropical forest plantations.